A Comprehensive Appraisal of the Factors Impacting Construction Project Delivery Method Selection: A Systematic Analysis. Issue 2 (4th March 2023) - Zhong, QingPing; Tang, Hui; Chen, Chuan; Igor, Martek
ABSTRACT: Construction projects may be procured by various means: design-build (DB), design-bid-build (DBB), construction management at risk (CM-at risk), and integrated project delivery (IPD), among many others. Each approach must be considered in selecting the most appropriate procurement strategy for any specific project. Thus, in making that choice, a selection approach along with selection criteria need to be considered. This study seeks to reassert clarity by consolidating the available literature on factors impacting project delivery selection and presenting a definitive, comprehensive list of those factors. The approach relies on systematic analysis. An initial retrieved 224 papers across 53 journals was reduced to 45 papers relevant to construction projects. These each offered between four to 39 factors. An examination and rationalization of themes distilled to a definitive 22 criteria and 35 sub-criteria. Chief among these, in descending order of reported frequency, were: owner related issues, contractor issues, time, cost, quality, contract disputes, risk, market conditions, regulation, complexity, innovation, scope, site, community support, project size, project type, resource availability, natural disasters, political impact, sustainability, culture, and safety. The factors will vary project-to-project, and a discussion of the impacts of these factors on the project delivery method selection is offered.